A British Experiment in the Control of Competition: The Coal Mines Act of 1930 - Lucas, Arthur F. (Quarterly Journal of Economics, 1934)
I. Introduction: Position of the British coal industry in 1929, 419; Provisions of the Act of 1930, 420; Nature of the machinery established, 421. — II. Regulation of Output: Procedure, 422; Adjustment of output to market conditions, 424; District allotments, 425; Individual quotas, 425; Compliance, 428. — III. Control of Prices: Procedure, 428; Difficulties encountered, 429; Results, 432; Lack of compliance, 433. — IV. Reorganization of the Industry: The Coal Mines Reorganization Commission, 434; Failure of compulsory combination, 437. — V. Summary and Conclusion: Results of the Act, 438; Obstacles, 438; Attitude toward the Act, 439; the social interest, 440; the Act as a permanent policy, 440.